HUBUNGAN MOTIVASI BELAJAR DENGAN KEMAMPUAN NUMBER SENSE SISWA KELAS V SDN 80 PEKANBARU - Lestari, Tania Willa; Putra, Zetra Hainul; Alpusari, Mahmud (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2024)
The purpose of this study was to determine the relationship between learning motivation and the Number sense ability of fifth grade students at SDN 80 Pekanbaru. This type of research is using correlation research, the subjects in this study are fifth grade students of Elementary School 80 Pekanbaru. The data in this study were collected using questionnaires and tests, and analyzed using SPSS 24.0. The results of data analysis can be concluded that the product moment correlation calculation results are known sig. (2-tailed) between learning motivation (x) and number sense (y) is 0.000 of 0.773, so it can be concluded that there is a relationship between learning motivation and number sense variables. Because the r count in this analysis is positive, it means that the relationship between the two variables is positive.